Study on the relationship between PTSD and academic control and academic emotion in primary and middle school students after flood disaster - Zhao, Lili; Wang, Haiyan; Wang, Kangning; Shen, Chengxuan; Tao, Mingda (Frontiers in Psychology, 2024)
Purpose To explore the relationship between post-traumatic stress disorder (PTSD) and students’ academic control and academic emotion in the aftermath of a flood disaster. The findings will offer educators and relevant departments valuable insights to understand and facilitate the restoration of learning capabilities among students affected by the disaster. Methods This study employed a combined approach of questionnaire surveys and longitudinal tracking. Students from Guangling Primary and Secondary School (Shouguang City, Weifang, Shandong Province) participated in surveys administered in September 2018, December 2018, and September 2019. The instruments utilized included the Post-Disaster Trauma Assessment Questionnaire, the Adolescent Academic Control Scale, and the mathematical version of the Achievement Emotions Questionnaire. Data analysis involved two-factor correlation and mediation effect testing. Results Significant differences were observed in overall PTSD scores and its three dimensions between the 1-week and 1-year post-disaster assessments. Both the average PTSD score and the detection rate were higher 1 year after the disaster compared to the first week. Students’ academic control demonstrated a strong positive correlation with positive academic emotions and a significant negative correlation with anxiety-related academic emotions. Cross-lagged regression analysis indicated a predictive relationship: academic control measured 3 months post-disaster significantly predicted academic emotions at the 9-month assessment, and conversely, academic emotions at the 3-month point were predictive of academic control at 9 months. In addition, academic control appears to play a complete mediating role in the relationship between PTSD and academic emotions. Conclusion Students exhibited a range of PTSD symptoms following the disaster, with a higher prevalence noted in the first year compared to the initial week. PTSD negatively affects academic standing in these students, and is predictive of both their sense of academic control and their emotional responses to learning. Crucially, academic control and academic emotions exhibit a strong correlation and can mutually affect one another. Interventions aimed at reducing PTSD symptoms, cultivating positive academic emotions, and strengthening students’ sense of academic control must therefore consider the relationship between these factors. This holistic approach will enhance psychological well-being and improve academic performance.